In vitro comparative analysis of the cytotoxic effects of brassica rapa & solanum tuberosum extracts coupled with sonodynamic therapy on MCF-7 breast cancer cell lines - Panlaqui, Paolo Miguel F. (Animo Repository, 2022)
In the Philippines, women have the highest breast cancer prevalence amongst Asian countries. Due to the dangerous side effects of existing treatments, alternative methods such as low intensity non-invasive treatments have been researched upon. In this study, sonodynamic therapy was coupled with Brassica rapa (Bok Choy) and Solanum tuberosum (Potato) extracts on MCF-7 breast cancer cell lines. First, the cytotoxicity characteristic of the vegetable extracts were examined using serial dilution, cytotoxic index computation, and determination of IC50 values through One-Way ANOVA. Tamoxifen was used as the point of comparison of how cytotoxic the crude vegetable extracts are resulting in IC50 values of 43.52 μL and 40.10 μL for bok choy and potato respectively. Afterwards, a new batch of MCF-7 cells were treated with bok choy (44 μL) or potato (40 μL) extracts coupled with ultrasound frequencies of 1 MHz, 2 MHz, and 4 MHz for 60 seconds then incubated for 24 hours. The 96 well plate was divided into four quadrants, each sonicated with a specific frequency with one left not sonicated in order to compare how effective the combined treatment was. Results showed that 1 MHz for both extracts were the most effective with synergistic cell death increases of 11.61% for potato and 16.49% for bok choy. One-way ANOVA, Dunnett’s test, and Tukey’s test were performed to see which treatment groups had similar and different effects. Results from the paired t-test of the three highest CI% values per combined treatment emphasized the difference in each treatment’s effect on MCF-7 cells. Overall, bok choy coupled with 1 MHz ultrasound was the most effective. Significant findings of the study may be utilized and further refined to explore the potential of SDT coupled methods as an alternative non-invasive treatment on breast cancer.